2008
DOI: 10.2459/jcm.0b013e3282f85bda
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of continuous and intermittent myocardial topical negative pressure

Abstract: No statistically significant difference was found between microvascular blood flow during 20 min of continuous and intermittent topical negative pressure at -50 mmHg in this porcine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Lindsted, et al strongly advocate placing multiple nonadherent layers between the foam dressing and the myocardial tissues. Increased flow occurred in normal, ischemic, and ischemic‐reperfused epicardium in their model 17,18 . This blood flow increase secondary to negative pressure was seen during hypothermia as well 19 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Lindsted, et al strongly advocate placing multiple nonadherent layers between the foam dressing and the myocardial tissues. Increased flow occurred in normal, ischemic, and ischemic‐reperfused epicardium in their model 17,18 . This blood flow increase secondary to negative pressure was seen during hypothermia as well 19 .…”
Section: Discussionmentioning
confidence: 88%
“…Increased flow occurred in normal, ischemic, and ischemic-reperfused epicardium in their model. 17,18 This blood flow increase secondary to negative pressure was seen during hypothermia as well. 19 While this is an attractive explanation for the protective effects observed in the present study, there is as yet no direct evidence that the change in microvascular blood flow occurs beyond the epicardial surface.…”
Section: Extensive Laboratory and Clinical Studies Have Addressed Thementioning
confidence: 89%
“…While other investigators have reported increases in epicardial blood flow within seconds of applying low (−50 mmHg), but not high (−125 mmHg), magnitudes of negative pressure, our data show the opposite phenomenon. They also observed an increase in epicardial blood flow in normal, ischemic, and ischemic‐reperfused epicardium and showed that the effect of negative pressure on blood flow was a function of distance from the source of negative pressure . While there are differences in the details of both methodology and results, both groups have demonstrated an effect of negative pressure on blood flow.…”
Section: Discussionmentioning
confidence: 98%
“…It was in practice in medical and biological trials in the last two decades (Table 2). Lindstedt et al (2008) compared the direct use of continuous negative pressure versus INP on bovine hearts and concluded that both the techniques significantly increased the local circulation into the cardiac muscle. [48] Campisi et al (2015) documented the beneficial role of INP as adjunct to lymphodema management.…”
Section: Cuppingmentioning
confidence: 99%
“…Lindstedt et al (2008) compared the direct use of continuous negative pressure versus INP on bovine hearts and concluded that both the techniques significantly increased the local circulation into the cardiac muscle. [48] Campisi et al (2015) documented the beneficial role of INP as adjunct to lymphodema management. [49] Sundby et al operated INP through an air tight chamber to the lower limbs of 23 healthy volunteers; the experiment resulted in increased circulatory flow into the feet of subjects.…”
Section: Cuppingmentioning
confidence: 99%